1991
DOI: 10.1128/iai.59.12.4332-4337.1991
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of carotenoid production, decreased membrane fluidity, and resistance to oleic acid killing in Staphylococcus aureus 18Z

Abstract: Staphylococcus aureus is susceptible to killing by host-derived fatty acids. Studies were performed to test for a correlation between carotenoid production by S. aureus and protection against oleic acid. Oleic acid killing of cells grown in carotenoid expression medium was determined as the dosage of oleic acid in 2 M NaCl-2 mM EDTA that would kill 20% of the cells in 60 min at 37°C (i.e., the 20% lethal dose). Compared with the wild-type strain (18Z), a carotenoid-deficient mutant strain (18Z-76) and strain 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 21 publications
(36 reference statements)
1
60
0
1
Order By: Relevance
“…As carotenoids were shown to have a direct protective effect against oleic acid killing in S. aureus (Xiong & Kapral, 1992), this raises the question of a potential influence of oleic acid on sigB signaling. In agreement with previous studies showing the effects of oleic acid on planktonic bacteria (Chamberlain et al, 1991;Xiong & Kapral, 1992;Xiong et al, 1993), our live/dead experiments performed with planktonic UAMS-1 and its DsigB mutant suggest a sigB-dependent resistance against oleic acid killing. However, the adherent bacterial population was affected by oleic acid independently of sigB expression as shown by the transcript levels of asp23 used to indirectly quantify the active form of SigB (Senn et 2005).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As carotenoids were shown to have a direct protective effect against oleic acid killing in S. aureus (Xiong & Kapral, 1992), this raises the question of a potential influence of oleic acid on sigB signaling. In agreement with previous studies showing the effects of oleic acid on planktonic bacteria (Chamberlain et al, 1991;Xiong & Kapral, 1992;Xiong et al, 1993), our live/dead experiments performed with planktonic UAMS-1 and its DsigB mutant suggest a sigB-dependent resistance against oleic acid killing. However, the adherent bacterial population was affected by oleic acid independently of sigB expression as shown by the transcript levels of asp23 used to indirectly quantify the active form of SigB (Senn et 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Despite several in vitro studies that analyzed the effects of oleic acid on S. aureus (Chamberlain et al, 1991;Xiong & Kapral, 1992;Xiong et al, 1993), the potential of oleic acid as a bactericidal agent on S. aureus remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids are lipophilic agents that are incorporated into the bacterial membrane. Chamberlain et al (1991) reported that carotenoids could influence cell membrane fluidity and decrease the sensitivity of Staph. aureus to oleic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Chamberlain et al . () reported that carotenoids could influence cell membrane fluidity and decrease the sensitivity of S. aureus to oleic acid. This finding implies that carotenoid production in LAB also may lead to changes in membrane fluidity.…”
Section: Discussionmentioning
confidence: 99%